New records and five new species of sipunculans (Sipuncula) from the central and northwestern Mexican Pacific - Gómez-Vásquez, Julio D. (European Journal of Taxonomy, 2024)
Sipuncula are marine unsegmented worms that can be found in benthic habitats, from shallow to deep-sea waters. In Mexico these worms have been scarcely studied. Among nine studies in the entire Mexican Pacific coasts, seven are from the central and northwestern Mexican Pacific. For over 80 years, only 24 species have been recorded. To improve the knowledge of the sipunculans from the central and northwestern Mexican Pacific, 501 specimens from three scientific collections of Mexico were revised. The specimens were collected by diverse methods from intertidal, subtidal, and bathyal depths ( 1000 m), from 27 locations along the central and northwestern Mexican Pacific. Sixteen taxa belonging to nine genera and five families were identified. One species is recorded for the first time in the Mexican Pacific and five new species are described, one from intertidal and shallow subtidal depths: Phascolosoma (Phascolosoma) azteca sp. nov.; two from subtidal depths: Phascolion (Lesenka) salgadoi sp. nov. and Sipunculus (Sipunculus) bastidai sp. nov.; and two from bathyal depths: Apionsoma (Apionsoma) silviae sp. nov. and Apionsoma (Edmondsius) hendrickxi sp. nov.